Hardy's poetic vision in "The Dynasts" : the diorama of a dream - Dean, Susan, 1937- (Princeton University Press, 1977)
Susan Dean uses Hardy's own metaphor-the diorama of a dream-to interpret The Dynasts, his largest and last major composition. She shows that the poem presents a model of the human mind. In that mind is enacted an event (the war with Napoleon) and, simultaneously, the watching of that event. The author provides a reading of the poem in visual-dramatic terms, using the diorama stage as the vehicle for the poet's field of vision. She then defines various visual dimensions, the relationships between them, and the various ways in which they can be seen and understood. Her interpretation draws on Hardy's autobiography and critical essays.Originally published in 1977.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Keywords: Hardy, Thomas, -- 1840-1928. -- Dynasts.; Napoleon -- I, -- Emperor of the French, -- 1769-1821 -- In literature.; Napoleon -- I, -- Emperor of the French, -- 1769-1821; Dynasts (Hardy, Thomas); Napoleonic Wars, 1800-1815 -- Literature and the wars.; Historical drama, English -- History and criticism.; Théâtre historique anglais -- Histoire et critique.; DRAMA -- European -- English, Irish, Scottish, Welsh.; FICTION -- General.; War and literature; Historical drama, English; Literature; 1800-1815; Criticism, interpretation, etc.